Military Art of The Peoples of Central Asia Against the Troops of Genghis Khan in The Middle Ages (Texas Journal of Multidisciplinary Studies, 2024)
The article talks about the peoples of Central Asia in the Middle Ages against the aggressive actions of the troops of Genghis Khan/ o the tactics used by the two sides, tactical techniques, form, methods of combat by the Khorezmshah and Mongols.